Vascular risk factors for idiopathic normal pressure hydrocephalus: a systematic review and meta-analysis - Cai, Hanlin; Yang, Feng; Gao, Hui; Huang, Keru; Qin, Linyuan; Wang, Ruihan; Liu, Yi; Zhou, Liangxue; Hao, Zilong; Zhou, Dong; Chen, Qin (Frontiers in Neurology, 2023)
Objective Idiopathic normal-pressure hydrocephalus (iNPH) is a treatable cause of dementia; however, its etiology and pathogenesis remain poorly understood. The objective of this study was to investigate the prevalence and impact of vascular risk factors in patients with iNPH compared to a control cohort to better understand the potential mechanisms and preventive measures. Methods We systematically searched PubMed, Web of Science, Embase, and the Cochrane Library (from inception to December 20, 2022) for studies reporting vascular risk factors for the development of iNPH. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using random-effects models. Results After screening 1,462 articles, 11 case-control studies comprising 1,048 patients with iNPH and 79,668 cognitively unimpaired controls were included in the meta-analysis. Our data showed that hypertension (N = 991, OR = 2.30, 95% CI 1.64 to 3.23, I2= 64.0%), diabetes mellitus (DM) (N = 985, OR = 3.12, 95% CI 2.29 to 4.27, I2= 44.0%), coronary heart disease (CHD; N = 880, OR = 2.34, 95% CI 1.33 to 4.12, I2= 83.1%), and peripheral vascular disease (N = 172, OR = 2.77, 95% CI 1.50 to 5.13, I2= 0.0%) increased the risk for iNPH, while overweight was a possible factor (N = 225, OR = 2.01, 95% CI 1.34 to 3.04, I2= 0.0%) based on the sensitivity analysis. Smoking and alcohol consumption were not associated with iNPH. Conclusions Our study suggested that hypertension, DM, CHD, peripheral vascular disease, and overweight were associated with iNPH. These factors might be involved in the pathophysiological mechanisms promoting iNPH. These findings require further investigation in future studies. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, CRD42022383004.